TINJAUAN KETEPATAN PUTUSAN HAKIM DALAM MEMUTUS PERKARA SENGKETA MEREK TERHADAP PEMBATALAN MEREK TERDAFTAR PERTAMA BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 375 K/PDT.SUS-HKI/2020 - Jessica Candakentjana; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
At this time, Intellectual Property Rights plays an important role in this industry. In the world of commerce, a brand is a form of intellectual property rights that has an important role because a brand is used to distinguish the origins of a product and service. Trademarks as a form of intellectual work play an important role in preventing unfair competition so that trademarks must be registered. The registration of trademark is a form of legal protection that creates legal certainty, so Indonesia adopts a constitutive system which determines that trademark rights can only be protected by the law if they are registered. Legal protection of trademark in Indonesia is only given to trademark owners who register their trademarks for the first time, in the principle, first-to-file. However, Budiman Tjoh as the owner who register the trademark for the first time did not feel the protection of trademarks on the first to file principle. The method used in this study is using normative legal research methods. The purpose of this study is to find out the legal protection of a first registered mark. The research data shows that the judge in deciding the trademark dispute is not right, because The judge prefers to consider that a trademark registered long after the Defendant's mark was registered is a well-known mark than consider the principle of first-to-file and the provisions stipulated in the Trademark Law, such as the stipulation on the time period for filing a lawsuit for cancellation.